Introduction to Strategy-as-Practice - Jarzabkowski, Paula; Seidl, David (Henry Stewart Talks, 2012)
Foundations of S-as-P, Strategy and economics, Strategy process, The practice turn, Definition, Three notions of practice, A research framework, A framework for studying S-as-P, Entwining macro and micro, Pluralism of theories, Theoretical resources, Methodological choices, Resources
Reviewed at 2017/09/03